Prevalence and Correlates of Non-Dating Sexual Violence, Sexual Dating Violence, and Physical Dating Violence Victimization among U.S. High School Students during the COVID-19 Pandemic: Adolescent Behaviors and Experiences Survey, United States, 2021 - Krause, Kathleen H. (Journal of interpersonal violence, 2023)
The COVID-19 pandemic created an environment of disruption and adversity for many adolescents. We sought to establish the prevalence of non-dating sexual violence, sexual dating violence, and physical dating violence victimization among adolescents during the COVID-19 pandemic and to investigate whether experiences of disruption and adversity placed adolescents at greater risk for these forms of interpersonal violence. We conducted a secondary analysis of data from the Adolescent Behavior and Experiences Survey, collected January to June 2021 from a nationally representative sample of U.S. high school students (N = 7,705). Exposures included abuse by a parent; economic, housing, and food and nutrition insecurity; interpersonal connectedness; and personal well-being. Among female students, 8.0% experienced non-dating sexual violence; 12.5% experienced sexual dating violence; and 7.7% experienced physical dating violence. Among male students, 2.2% experienced non-dating sexual violence; 2.4% experienced sexual dating violence; and 4.9% experienced physical dating violence. Among female students, both emotional and physical abuse by a parent was related to non-dating sexual violence, emotional abuse was related to sexual dating violence, and physical abuse was related to physical dating violence. Among males, emotional abuse by a parent was related to physical dating violence and physical abuse by a parent was related to sexual dating violence. Hunger was associated with sexual and physical dating violence among female students and homeless was associated with physical dating violence among male students. Although there were differences by sex, abuse by a parent, hunger, and homelessness created precarity that may have increased the likelihood that adolescents would be exposed to risky peer or dating relationships. Adolescents need support that stops and prevents experiences of non-dating sexual and dating violence connected to interventions that address adversities experienced during the COVID-19 pandemic.